"Adult" as a Concept for Young People Building their Life Course. Issue 3 (3rd March 2016) - Pavlenko, E.S.
Abstract : The structure of Russians' life course has never been studied in depth; the only exception is demographic studies regarding marital status and age at childbirth. Principles that define life trajectories should also be examined. The "adult" concept is one of a number of important concepts in the general structure of life planning. This article presents an agenda for future research based on several case studies obtained during a longitudinal study of educational and occupational trajectories. Studying the transition into adulthood is an important resource for understanding the modern times. However, another option is also possible. This concept of transition into adulthood can also be considered as a phenomenon of contemporary culture. The research perspective of cultural sociology, whose methodology is described as structural hermeneutics, can serve these purposes. Structural hermeneutics refers to an analysis of the structure of senses both intersubjective and collectively shared. It is important to analyze how the adult concept is used with regard to the structure of the life course in materials from Russian studies, with account for the ambivalence of this concept and research conducted in other countries.